Pemahaman nilai-nilai spiritual dalam pendidikan kedokteran: A literature review - Syafitri, Khusnul; Royani, Ida; Kartika, Andy Visi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Spiritual values ​​are an important dimension of humanistic and holistic medical practice. In medical education, spirituality is increasingly viewed as relevant because it contributes to student character development, such as empathy, resilience, integrity, and patient-centered care orientation. However, the integration of spiritual values ​​into medical curricula remains variable and has not been widely standardized. Purpose: To conduct a systematic review of the literature on understanding spiritual values ​​in medical education related to character development in medical students. Method: This study used a structured, domain-based literature review approach. Analysis was conducted on eight relevant scientific articles, including systematic reviews, quasi-experimental studies, cross-sectional studies, exploratory studies, case studies, and grounded theory. Each article was analyzed based on theoretical domains and research gaps to gain a comprehensive understanding of the role of spirituality in medical education. Results: The integration of spiritual values ​​in medical education is positively associated with student character development, specifically empathy, resilience, spiritual well-being, professional integrity, and holistic care competency. Structured spiritual training programs and curricula have been shown to improve student competence and confidence, although most research relies on self-report instruments and short-term assessments. Conclusion: Spirituality is a crucial component in the character development of medical students and needs to be systematically integrated into medical education. Developing a curriculum based on spiritual values ​​has the potential to produce future physicians who are not only clinically competent but also possess character, empathy, and integrity. Keywords: Character Development; Medical Education; Medical Students; Spiritual Values. Pendahuluan: Nilai spiritual merupakan salah satu dimensi penting dalam praktik kedokteran yang humanistik dan holistik. Dalam pendidikan kedokteran, spiritualitas semakin dipandang relevan karena berkontribusi terhadap pembentukan karakter mahasiswa, seperti empati, resiliensi, integritas, dan orientasi pelayanan berpusat pada pasien. Namun, integrasi nilai spiritual dalam kurikulum kedokteran masih bervariasi dan belum terstandarisasi secara luas. Tujuan: Untuk mengkaji secara sistematis literatur pemahaman nilai-nilai spiritual dalam pendidikan kedokteran tentang pembentukan karakter pada mahasiswa kedokteran. Metode: Penelitian ini menggunakan pendekatan domain-based structured literature review. Analisis dilakukan terhadap 8 artikel ilmiah yang relevan, mencakup systematic review, quasi-experimental study, cross-sectional study, eksploratory study, case study, dan grounded theory. Setiap artikel dianalisis berdasarkan domain teori insight dan gap penelitian untuk memperoleh pemahaman komprehensif mengenai peran spiritualitas dalam pendidikan kedokteran. Hasil: Integrasi nilai spiritual dalam pendidikan kedokteran berhubungan positif dengan pengembangan karakter mahasiswa, terutama empati, resiliensi, kesejahteraan spiritual, integritas profesional, dan kompetensi perawatan holistik. Program pelatihan dan kurikulum spiritual yang terstruktur terbukti meningkatkan kompetensi dan kepercayaan diri mahasiswa, meskipun sebagian besar penelitian masih bergantung pada instrumen self-report dan evaluasi jangka pendek. Simpulan: Spiritualitas merupakan komponen penting dalam pembentukan karakter mahasiswa kedokteran dan perlu diintegrasikan secara sistematis dalam pendidikan kedokteran. Pengembangan kurikulum berbasis nilai spiritual berpotensi menghasilkan calon dokter yang tidak hanya kompeten secara klinis, tetapi juga berkarakter, berempati, dan berintegritas. Kata Kunci: Mahasiswa Kedokteran; Nilai Spiritual; Pendidikan Kedokteran; Pengembangan Karakter.